School Environment on Students' Academic Achievement (Case Study at SMA Negeri 8 and SMAS Panjura Malang) - Zulfi Maulina Rahma; Yogi Dwi Satrio; Hari Wahyono; Agung Haryono (Universitas Pendidikan Ganesha, 2026)
Education plays a significant role in shaping the ideal future of society. Despite the immense benefits of education, achieving success in the field of education certainly requires significant effort. This study aims to analyze the influence of parental support, teacher roles, and school environment on students' academic achievement at SMAN 8 Malang and SMAS Panjura Malang. This research uses a quantitative approach with the multiple linear regression method. Data collection techniques used questionnaires distributed to 188 students as a sample, determined using the Slovin formula. The t-test results show that at SMAN 8 Malang, no variable significantly affects students' academic achievement. However, at SMAS Panjura Malang, the school environment variable significantly influences academic achievement with a negative direction. This illustrates that although the school environment has an influence on students' academic performance, the quality of that environment is not yet optimally supportive. Meanwhile, parental support and the role of teachers in both schools did not show a significant influence. This finding confirms the importance of building synergy between school authorities, teachers, and parents in creating a conducive learning environment to support students' academic achievement.